![j=-4](https://img.qammunity.org/2023/formulas/mathematics/high-school/dan6otwjqb89oflf7ekztr0ymfq6mpehpa.png)
Step-by-step explanation
![2j-4=-12](https://img.qammunity.org/2023/formulas/mathematics/high-school/s18kq5723xsnwwxa3qorier6vt39xia7ba.png)
to solve we need to siolate j, so
Step 1
apply the addition property of equality, it says If two expressions are equal to each other, and you add the same value to both sides of the equation, the equation will remain equal.
hence
![\begin{gathered} 2j-4=-12 \\ \text{add 4 in both sides} \\ 2j-4+4=-12+4 \\ 2j=-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/53gmyw7jupd26es79k3s3k93dnan99zxqq.png)
Step 2
now, we need to remove the factor 2, to do that, let's apply the division property of equality,it states that when we divide both sides of an equation by the same non-zero number, the two sides remain equal,so
![\begin{gathered} 2j=-8 \\ \text{divide both sides by 2} \\ (2j)/(2)=(-8)/(2) \\ j=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/endze60eqo3zgrww1iri94syr0h8waz6xu.png)
therefore, the answer is
![j=-4](https://img.qammunity.org/2023/formulas/mathematics/high-school/dan6otwjqb89oflf7ekztr0ymfq6mpehpa.png)
I hope this helps you